Analysis of Mercury Concentration in Food Crops Around the Lebong Regency Gold Mine - Fatimatuzzahra, Fatimatuzzahra; Sri Astuti, RR; Satriawan, Dedi; Sipriyadi, Sipriyadi; Istikhomah, Sekar; Eva Nadya Purba, Juwita; Farid Fadhlullah, Muhammad; Wahyu Nengsih, Anisa; Shofi, Muh.; Saputra, Alanindra (Biosfer: Jurnal Tadris Biologi, 2025)
This study aims to inventory the types of food crops growing around tailings ponds and to quantify mercury concentrations in food crop tissues growing in the area around the gold mine. The samples taken are plants consumed by residents. Mercury content testing uses a mercury analyzer. The results of the study showed that from 4 observation locations, a total of 11 types of food crops were found, all of which contained mercury (Hg) with a concentration range of 0.01-0.54 mg/kg. Similarly, the soil as a growing medium contains quite high levels of mercury at location 1, namely 54.36 mg/kg, and the lowest at location 3 at 0.12 mg/kg. The concentration of mercury in vegetable leaves is much higher than in other organs such as tubers, flowers, and fruits. Furthermore, to plant plants for consumption, it is best to pay attention to the condition of the growing medium, as a prevention of heavy metal (mercury) contamination, such as the environment (air, soil, water) that is far from waste retention ponds or waste discharge streams containing heavy metals (mercury). Analisis Konsentrasi Merkuri pada Tanaman Pangan di Sekitar Tambang Emas Kabupaten Lebong ABSTRAK: Penelitian ini bertujuan untuk menginventarisasi jenis tanaman pangan yang tumbuh disekitar kolam penampungan limbah (tailing) dan untuk mengkuantifikasi konsentrasi merkuri dalam jaringan tanaman pangan yang tumbuh di area sekitar tambang emas. Sampel yang diambil merupakan tanaman yang memang dikonsumsi oleh warga setempat. Uji kandungan merkuri menggunakan mercury analyzer. Hasil penelitian menunjukkan dari 4 lokasi pengamatan, ditemukkan Sebanyak 11 jenis tanaman pangan yang semuanya mengandung merkuri (Hg) dengan kisaran konsentrasi 0,01-0,11 mg/kg. Demikian pula, tanah sebagai media tanam mengandung kadar merkuri yang cukup tinggi di lokasi 1, yaitu 54,36 mg/kg, dan paling rendah dilokasi 3 sebesar 0,12 mg/kg. konsentrasi merkuri dalam daun sayuran jauh lebih tinggi dibandingkan organ lain seperti tuber, bunga, dan buah. Selanjutnya, untuk menanam tanaman yang akan dikonsumsi sebaiknya memperhatikan kondisi media tumbuh, sebagai pencegahan dari kontaminasi logam berat (merkuri), seperti lingkungan (udara, tanah,air) yang jauh dari kolam penampungan limbah maupun aliran pembuangan limbah yang mengandung merkuri.